Biological active metabolites from microalgae for healthcare and pharmaceutical industries: a comprehensive review - Tengku Ibrahim, Tengku Nilam Baizura; Feisal, Nur Azalina Suzianti; Kamaludin, Noor Haziqah; Cheah, Wai Yan; How, Vivien; Bhatnagar, Amit; Ma, Zengling; Show, Pau Loke (Elsevier, 2023)
Microalgae are photoautotrophic microorganisms that comprise species from several phyla. Microalgae are promising in producing a variety of products, including food, feed supplements, chemicals, and biofuels. Medicinal supplements derived from microalgae are of a significant market in which compounds such as -carotene, astaxanthin, polyunsaturated fatty acids (PUFA) such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), and polysaccharides such as “glucan, are prominent. Microalgae species that are commonly applied for commercial productions include Isochrysis sp., Chaetoceros (Chlorella sp.), Arthrospira sp. (Spirulina Bioactive), and many more. In this present review, microalgae species that are feasible in metabolite production are summarized. Metabolites produced by microalgae as well as their prospective applications in the healthcare and pharmaceutical industries are comprehensively discussed. This evaluation is greatly assisting industrial stakeholders, investors, and researchers in making business decisions, investing in ventures, and moving the production of microalgae-based metabolites forward.